2014
DOI: 10.1159/000368842
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2-Meditated Multidrug Resistance and Tumor-Initiating Capacity of Side Population Cells from Colon Cancer

Abstract: SummaryBackground: Recent studies have reported that the presence of cancer stem cells (CSCs) has major implications in the treatment of cancer and is responsible for tumor relapse. In the current study, we identified and characterized colon CSC-like side population (SP) cells from colon cancer tissue. Materials and Methods: The colon cancer samples were subjected to fluorescence-activated cell sorting (FACS) based on Hoechst 33342 dye exclusion for the purification of SP cells. The sorted SP cells were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…The ATP-binding cassette transporter (ABC) family induces resistance to chemotherapy in several malignancies. 42,4953 Recently, based on the expression of the ABC family member ABCB5, melanoma cancer stem cells (MCSCs) were identified and it was shown that ABCB5 maintains melanoma-initiating cells through a proinflammatory cytokine signaling circuit. 54 Wang et al 50 showed that Panc-1 pancreatic CSCs express high levels of CD133/CD44/Oct4/Nestin compared to Panc-1 cells, are resistant to gemcitabine, and express high levels of P-gp as well as high anti-apoptotic proteins, but exhibit weak proliferative potential.…”
Section: Mechanisms Of Death Resistance In Cancer Stem Cellsmentioning
confidence: 99%
“…The ATP-binding cassette transporter (ABC) family induces resistance to chemotherapy in several malignancies. 42,4953 Recently, based on the expression of the ABC family member ABCB5, melanoma cancer stem cells (MCSCs) were identified and it was shown that ABCB5 maintains melanoma-initiating cells through a proinflammatory cytokine signaling circuit. 54 Wang et al 50 showed that Panc-1 pancreatic CSCs express high levels of CD133/CD44/Oct4/Nestin compared to Panc-1 cells, are resistant to gemcitabine, and express high levels of P-gp as well as high anti-apoptotic proteins, but exhibit weak proliferative potential.…”
Section: Mechanisms Of Death Resistance In Cancer Stem Cellsmentioning
confidence: 99%
“…51,52 and an elevated expression of anti-apoptotic proteins. 4 • As such, CSCs exhibit increased resistance to standard radio-and chemotherapies.…”
Section: Characteristics Of Cancer Stem Cellsmentioning
confidence: 99%
“…Besides introduced markers listed in Table 1 Apart from in vitro studies, analyzing clinical samples revealed that CD44 could be used in combination with clinicopathological information to improve the OSCC prognosis, since its overexpression, in tumor samples and peripheral blood of OSCC patients, was correlated to poor prognosis LGR5 [152,153] EpCAM [120] BMI1 [119,218] CD24 [122,125] OCT4 [118,119] SOX2 [118,119,[149][150][151] NANOG [118,119] Colon and rectum CD44 [166,[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198]200] CD133 [161-165, 171-178, 186-188, 232] ABCG2 [75,158,159] ALDH1 [198,[222][223][224]…”
Section: Oral Cavitymentioning
confidence: 99%
“…One of the first reports on CRC stem-like cells was the isolation of highly proliferative and therapy-resistant SP cells from CRC cell lines [75]. Later results have also introduced SP cells as stem-like CRC cells, due to their high proliferation, invasion, and tumorigenic abilities [158,159]. However, there is a report indicating that sorting for SP cells does not apply to colon CSCs, as both SP and NSP cells were clonogenic in vitro and tumorigenic in vivo and displayed similar differentiation potential and expression pattern for CD133, CD44, OCT4, and ABCG2 [160].…”
Section: Colon and Rectummentioning
confidence: 99%